Form, Function, And Meaning Of Fasade Ornament Design Malay Traditional Balai Building, Riau Province In Pekanbaru - Nofiyanti, Nofiyanti; Heldi, Heldi (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
The Riau Malay Traditional Hall building is a form of culture in the form of objects inherited by previous generations that still exist today. Where the Malay Traditional Hall building has become a symbol of Malay culture and also shows how the arts and creativity of the Malay community are in the field of ornamental design. The purpose of this research is to increase public understanding, especially the younger generation of Malays regarding the form, function, and meaning of the existing ornament designs at the Riau Malay Traditional Hall. With the increasing understanding of the community, especially the younger generation, it is expected to be able to properly preserve Malay culture, namely the Traditional Hall and its ornamental designs. The method used in this research is descriptive qualitative with sampling technique using purposive sampling. The results of this study are successful in describing and explaining how the forms of ornamental designs in the Riau Malay Traditional Hall building have three types of motifs, namely animal, plant, and geometric shapes. The function of the ornamental design in addition to beauty also has a symbolic function and usability function. Furthermore, there is also meaning in each ornament design that has the meaning of life and diversity in the Riau Malay community. Therefore, it is very important to understand the form, function, and meaning of the ornament design in the Riau Malay Traditional Hall building so that it can continue to maintain the preservation of ornament making and also the traditional Balai owned.